Humanizing Technology : Rekonstruksi Pendidikan Akhlak di Tengah Hegemoni Algoritma Era Society 5.0 - Nur Khairani; Tiana Atika; Herlini Puspika Sari (Jurnal Pendidikan UNIGA, 2026)
This research is motivated by the phenomenon of algorithmic hegemony in the Society 5.0 era, which has the potential to erode human values and the moral integrity of students. The aim of this research is to formulate a reconstruction of moral education as an effort toward "humanizing technology" so that digital progress remains based on noble character. The research method used is qualitative with the type of library research, where data is analyzed descriptively and analytically through classic and contemporary literary sources. The research results show that the reconstruction of moral education can be achieved through the internalization of inner virtue values and the strengthening of four main character pillars: wisdom, courage, self-control, and justice. The research findings emphasize that moral education in the Society 5.0 era must transform from a mere transfer of knowledge into a process of digital ethics habituation capable of forming moral immunity against algorithmic manipulation. Thus, technology is positioned as an instrument supporting the common good, while humans maintain full control as wise moral subjects in cyber interactions. Keywords: Moral Education, Society 5.0, Humanizing Technology, Algorithmic Hegemony.